Quantitative analysis of glycerol in dicarboxylic acid-rich cutins provides insights into Arabidopsis cutin structure. (October 2016) - Yang, Weili; Pollard, Mike; Li-Beisson, Yonghua; Ohlrogge, John
Abstract: Cutin is an extracellular lipid polymer that contributes to protective cuticle barrier functions against biotic and abiotic stresses in land plants. Glycerol has been reported as a component of cutin, contributing up to 14% by weight of total released monomers. Previous studies using partial hydrolysis of cuticle-enriched preparations established the presence of oligomers with glycerol-aliphatic ester links. Furthermore, glycerol-3-phosphate 2- O -acyltransferases ( sn -2-GPATs) are essential for cutin biosynthesis. However, precise roles of glycerol in cutin assembly and structure remain uncertain. Here, a stable isotope-dilution assay was developed for the quantitative analysis of glycerol by GC/MS of triacetin with simultaneous determination of aliphatic monomers. To provide clues about the role of glycerol in dicarboxylic acid (DCA)-rich cutins, this methodology was applied to compare wild-type (WT) Arabidopsis cutin with a series of mutants that are defective in cutin synthesis. The molar ratio of glycerol to total DCAs in WT cutins was 2:1. Even when allowing for a small additional contribution from hydroxy fatty acids, this is a substantially higher glycerol to aliphatic monomer ratio than previously reported for any cutin. Glycerol content was strongly reduced in both stem and leaf cutin from all Arabidopsis mutants analyzed ( gpat4 / gpat8, att1-2 and lacs2-3 ). In addition, the molar reduction of glycerol was proportional to the molar reduction of total DCAs. These results suggest "glycerol-DCA-glycerol" may be the dominant motif in DCA-rich cutins. The ramifications and caveats for this hypothesis are presented. Graphical abstract: Methods for glycerol and aliphatic monomer analysis of cutin were optimized and used to show a 2:1 molar ratio of glycerol to dicarboxylic acids (DCAs) in Arabidopsis DCA-rich cutins. "Glycerol-DCA-glycerol" is proposed as a dominant structural motif in such cutins, and that this unit is connected to the cell wall through ester bonds to form a heteropolymer. Highlights: A GC/MS stable isotope-dilution assay was developed for glycerol quantification. Glycerol and aliphatic monomers were quantified for dicarboxylic acid-rich cutins. The molar ratio of glycerol to total dicarboxylic acids in Arabidopsis cutin is 2:1. Analysis of mutants in cutin biosynthesis confirmed the 2:1 molar ratio. "Glycerol-dicarboxylate-glycerol" is proposed as the dominant motif in such cutins.